Criminal Sanctions in Indonesian Taxation Law: Re-Evaluating Proportionality and Legal Certainty - Hartanto, Hartanto; Wahyandono, Matheas Prihargo (Fakultas Hukum Universitas Komputer Indonesia, 2025)
This study examines the implementation of criminal law policy within the field of taxation, with a particular emphasis on the application of the ultimum remedium principle and the implications of the repeal of Article 13A of the Law on General Provisions and Tax Procedures (UU KUP). In this context, taxation is understood as an integral part of criminal legal policy and the enforcement of law concerning tax-related offences that carry criminal consequences. The study aims to provide policy recommendations for relevant stakeholders in designing criminal enforcement strategies in taxation, ensuring that the ultimum remedium principle remains the central reference for maintaining proportionality and justice. The research employs a normative juridical approach, focusing on regulatory analysis and the examination of legal arguments regarding the impact of Article 13A’s removal on the direction of tax criminal law policy. The findings highlight that the presence of the ultimum remedium principle in tax law is essential to ensuring a balance between state interests and the protection of taxpayers' rights. The repeal of Article 13A may give rise to new dynamics in the practice of tax criminal enforcement, particularly in shaping enforcement strategies that are responsive to current socio-economic conditions